Over a million students use our free study notes to help them with their homework
Use product rule. d(uv)/dx = u dv/dx +v du/dxu=x du/dx=1v=e^x dv/dx=e^xd(xe^x)/dx = xe^x + e^x.1 = e^x(x+1)
To find the value of w, let x = w and y = -32. Substitute these values into the equation of the curve, C: y = (2x-3)^5 => -32 = (2(w) - 3 )^5. Note: the symbol, =>, means "implies that." F...
Firstly we can use the difference rule to split f'(x) into three components which we can consider separately. Then using the knowledge that the integral of x^n is 1/(n+1)*x^(n+1) we get the expression for...
a) We need to differentiate this equation using the quotient rule (Given that it is a fraction with an x term on both the top and bottom of the fraction). We assign the numerator and denominator as follow...
dx/dt = 3(t-1)2dy/dt = 3 + 16t-3dy/dx=(dy/dt)(dt/dx) dy/dx = 3 + 16t-3 / 3(t-1)2At t=2 dy/dx= (3 + 16/8) / 3 = 5/3 Gradient of the normal = -3/5with t=2 y...
←
158
159
160
161
162
→
Internet Safety
Payment Security
Cyber
Essentials